Meister Eckhart’s Non-standard natural theology - Vinco, Roberto (Neue Zeitschrift für systematische Theologie und Religionsphilosophie, 2016)
In this paper, I discuss Meister Eckhart’s approach to natural theology and specifically to the question of God’s existence. I argue that, according to the Eckhartian position, God’s existence is not to be regarded as the result of an (a posteriori or a priori) inference, but as metaphysical self-evidence. This non-inferential conception, based on a fundamental unity between natural theology and general metaphysics, constitutes an alternative to the standard Avicennian paradigm that lies at the heart of most of the natural-theological projects of the scholastic tradition.
Gesehen am 07.04.2021
Keywords: Gottesfrage; Metaphysik; Natürliche Theologie; Eckhart <Meister>